Sujeitos líricos na poesia brasileira marginal-periférica : o genocídio da população negra nas obras de Ricardo Aleixo e Dinha - Lovato, Francisco (2023)
This research intends to analyze in what way contemporary Brazilian marginalperipheral poetry re-presents the processes of concrete and symbolic genocide suffered by the black population in Brazil. For this purpose, we chose, as the corpus constituting this study, the brazilian poems Zero a Zero and Poema Pouco Poema, by the São Paulo poet Dinha, and the poems Na Noite Calunga do Bairro Cabula and Rosto, by the poet Ricardo Aleixo from Minas Gerais. Based on a bibliographical review, the works Cuidado com os poetas: literatura e periferia na cidade de São Paulo, by Lucía Tennina, and Polifonias marginais, organized by Ingrid Hapke, Mario Medeiros, Érica Peçanha and Lucía Tennina were released for a critical review of the marginal-peripheral literature category. In order to have a grounding of theoretical predictions that would enable to identify what are the constitutive properties of lyric language, the works Conhecimento da Literatura: Introdução aos estudos de Literatura by Carlos Reis, O arco e a lira, by Octávio Paz, and Conceitos fundamentais da poética, by Emil Staiger were used. In addition to this theoretical contribution from the literary field, the research bases its analyzes on the genocide of the black population in Brazil in the work O genocídio do negro brasileiro: the process of a masked racism, by Abdias Nascimento. The poems that make up the corpus of this research express in their speeches and poetic forms the pain and suffering of the deliberate extermination of the black population in Brazil. Both Dinha and Aleixo express a movement of interiorization in their works that dialogues with concrete facts of the empirical reality outside themselves. Thus, the lyrical subjects of poems are, according to Reis (2013), constituted by words and, through them, recreate and (re)present their and their peers’ realities in images, meanings, rhythms, emotions. In summary, this research seeks to undertake a theoretical-critical and thematic analysis of the Works that make up the corpus of this research